Republic of Poland : Review Under the Flexible Credit Line Arrangement-Press Release; Staff Report; and Statement by the Alternate Executive Director for the Republic of Poland. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Poland's performance under the Flexible Credit Line Arrangement. In recent years, Poland's macroeconomic policies have focused on further strengthening fundamentals and institutional frameworks. Fiscal consolidation has led to an exit from the Excessive Deficit Procedure. Monetary policy has been eased to help lift inflation. Financial sector supervision has been strengthened with a new macroprudential framework. Reserves are broadly adequate against standard metrics. The new government has pledged to maintain prudent policies, including gradual fiscal consolidation over the medium term, and to ensure the continued stability of the banking system. In the period ahead, it will be important to identify specific growth-friendly measures to underpin the fiscal adjustment and reduce implementation risk.